Evaluation of the SD Bioline TB Ag MPT64 test for identification of Mycobacterium tuberculosis complex from liquid cultures in Southwestern Uganda - Orikiriza, Patrick (Afr J Lab Med, 2017)
BACKGROUND: To confirm presence of Mycobacterium tuberculosis complex, some tuberculosis culture laboratories still rely on para-nitrobenzoic acid (PNB), a traditional technique that requires sub-culturing of clinical isolates and two to three weeks to give results. Rapid identification tests have improved turnaround times for mycobacterial culture results. Considering the challenges of the PNB method, we assessed the performance of the SD Bioline TB Ag MPT64 assay by using PNB as gold standard to detect M. tuberculosis complex from acid-fast bacilli (AFB) positive cultures. OBJECTIVES: The aim of this study was to determine the sensitivity, specificity and turnaround time of the SD MPT64 assay for identification of M. tuberculosis complex, in a setting with high prevalence of tuberculosis and HIV. METHODS: A convenience sample of 690 patients, with tuberculosis symptoms, was enrolled at Epicentre Mbarara Research Centre between April 2010 and June 2011. The samples were decontaminated using NALC-NaOH and re-suspended sediments inoculated in Mycobacterium Growth Indicator Tubes (MGIT) media, then incubated at 37 °C for a maximum of eight weeks. A random sample of 50 known negative cultures and 50 non-tuberculous mycobacteria isolates were tested for specificity, while sensitivity was based on AFB positivity. The time required from positive culture to reporting of results was also assessed with PNB used as the gold standard. RESULTS: Of the 138 cultures that were AFB-positive, the sensitivity of the SD MPT64 assay was 100.0% [95% CI: 97.3 – 100] and specificity was 100.0% (95% CI, 96.4 – 100). The median time from a specimen receipt to confirmation of strain was 10 days [IQR: 8–12] with SD MPT64 and 24 days [IQR: 22–26] with PNB. CONCLUSION: The SD MPT64 assay is comparable to PNB for identification of M. tuberculosis complex and reduces the time to detection.